Why We Should Build Software Like We Build Houses - Lamport, Leslie (Wired, 2013)
I was approached by an editor at Wired to write an article for them. After a great deal of discussion and rewriting, we finally came up with this compromise between what Wired wanted and what I was willing to sign my name to. The basic message of the piece is that, when programming, it's a good idea to think before you code. I was surprised when the posted comments revealed that this is a controversial statement.